Pemberdayaan Masyarakat Melalui Kegiatan Urban farming dan Pengelolaan sampah di Kelurahan Gunung Samarinda Baru: Community Empowerment Through Urban Farming Activities and Waste Management in the Gunung Samarinda Baru Village - Prabowo, Agung; Alif, Muhammad Ikhsan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Limited area for green open space is a common problem in densely populated areas in Indonesia. This also happened in Gunung Samarinda Baru Village; this area is one of the most densely populated areas and will continue to grow until now. These activities in the form of training and work practices are carried out through urban farming activities, namely hydroponic vegetable cultivation and compost processing from household waste. The activity started with a socialization approach regarding concepts and knowledge related to urban farming and compost management in the community. Furthermore, after they were familiar with the concept and urgency of urban farming and processing, we held training to give it directly to the community. It not only provides socialization and practice, but it also involves a monitoring process to determine the impact of the service activities that have been carried out. From the monitoring results, the community can take advantage of their green open space through vegetable growing activities using the hydroponic method. This is shown by the first harvest carried out with the community service team, as well as compost processing. This service activity is a good start for the community to maximize further the potential of green open spaces in their environment.